2016
DOI: 10.1111/jan.13152
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods systematic review exploring mentorship outcomes in nursing academia

Abstract: This review can inform the objectives of mentorship interventions and contribute to a more rigorous approach to studies that assess mentorship outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…In studies involving comparable populations in educational settings, peer mentoring has been shown to provide participants with a variety of developmental and psychosocial benefits, enabling them to better adapt to their learning environments [ 27 – 30 ]. Authors of a systematic review of mentoring in academic nursing found that, in general, peer-mentoring programs enabled nurses to develop collaborative peer relationships that reduced self-perceived stress [ 30 ]. Among healthcare professionals, and medical residents in particular, peer-mentoring relationships can increase social support and reduce symptoms of burnout [ 12 , 16 , 31 34 ] .…”
Section: Introductionmentioning
confidence: 99%
“…In studies involving comparable populations in educational settings, peer mentoring has been shown to provide participants with a variety of developmental and psychosocial benefits, enabling them to better adapt to their learning environments [ 27 – 30 ]. Authors of a systematic review of mentoring in academic nursing found that, in general, peer-mentoring programs enabled nurses to develop collaborative peer relationships that reduced self-perceived stress [ 30 ]. Among healthcare professionals, and medical residents in particular, peer-mentoring relationships can increase social support and reduce symptoms of burnout [ 12 , 16 , 31 34 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The initial design of the fellowship program was informed by a review of the literature on the changing profile of graduate education and on experiential training programs in the US, Europe and elsewhere (summarized in CHSPRA TMWG [2015a,b]). Delineation of the core issues about the mentorship component was based on a review of the literature on the role of mentorship in career development in business organizations, health systems and universities (Allen et al 2004;Claman 2010;Eby et al 2008;Eller et al 2014;Gagliardi et al 2014;Nowell et al 2017;Sambunjak et al 2006;Sherrill et al 2012;Tjan 2017;Tong and Kram 2013;Walsh and Borkowski 1999). Given that the HSI Fellowship program set clear objectives regarding the importance of supervision and mentorship but did not prescribe the details of what should be offered or how to do so, the Training Modernization Working Group (TMWG) identified an opportunity to study the initial years of the program in order to learn about the mentorship strategies that were used and to explore fellows' and supervisors' perspectives and experiences regarding the effectiveness and value of those strategies.…”
Section: Methodsmentioning
confidence: 99%
“…The Turkish study highlights the importance of mentoring in assisting students to manage stress by reducing anxiety and shifting from external control to internal control (Demir et al, 2014). A mentoring program in the US, 'MENTOR', is showing positive results for ethnically diverse nursing students, and both in Australia and New Zealand there is increasing evidence that mentoring provides a satisfying learning environment in a range of education and practice settings (Crooks, 2013;Harding & Mawson, 2017;Nowell, Norris, Mrklas, & White, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%